1993
DOI: 10.1073/pnas.90.22.10474
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus infection of human brain capillary endothelial cells occurs via a CD4/galactosylceramide-independent mechanism.

Abstract: Neuropathologic studies of AIDS patients have shown that brain capillary endothelial cells are a cellular target for human immunodeficiency virus (HIV) in vivo. We have established in vitro cultures of primary human brain capillary endothelial (HBCE) cells. Using this model system, we have shown a signifcant HIV infection of HBCE cells that is productive yet noncytopathic. The infection is mediated by a cellular interaction with gpl20 that does not involve CD4 or galactosylceramide. HIV infection of HBCE cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
122
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(130 citation statements)
references
References 45 publications
7
122
1
Order By: Relevance
“…As previously reported, we found that BMECs lack the entry receptor CD4 as well as GalCer ( Fig. 1A and B) (23,54). We also found that BMECs express low levels of both coreceptors CCR5 and CXCR4 ( Fig.…”
Section: Cell Surface Expression Of Proteoglycans On Primary Humansupporting
confidence: 88%
See 3 more Smart Citations
“…As previously reported, we found that BMECs lack the entry receptor CD4 as well as GalCer ( Fig. 1A and B) (23,54). We also found that BMECs express low levels of both coreceptors CCR5 and CXCR4 ( Fig.…”
Section: Cell Surface Expression Of Proteoglycans On Primary Humansupporting
confidence: 88%
“…Lastly, anti-CD4 antibodies (SIM2 and SIM.4) (100 l of culture supernatant per ml of each) failed to prevent HIV-1 attachment, entry, and transcytosis (Fig. 6), further suggesting that HIV-1 crosses the BBB in a CD4-independent manner as proposed previously (23,54). Note that we verified the potency of these entry inhibitors (Fig.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The blood-brain barrier (BBB) strictly regulates the transport of blood-borne cells and substances into the brain. Brain microvessel endothelial cells are a major component of the BBB and do not express CD4 receptor which HIV-1 uses to enter other cell types (Moses et al, 1993). Despite and absence of the CD4 receptor, HIV-1 can cross the BBB by two routes, the passage of cell free virus by adsorptive endocytosis (Banks et al, 2001) and the trafficking of infected immune cells across BBB (Persidsky et al, 1997).…”
Section: Introductionmentioning
confidence: 99%